Effect of Molecular Weight Reduction of Polypeptides on Angiotensin Converting Enzyme (ACE) Inhibitory Activity in Chicken Skin Hydrolysate (Collagen) - Babji, Abdul Salam; Daud, Nur Aliah; Husain, Salma Gulam (Journal of Nutritional Therapeutics, 2014)
Inhibition of Angiotensin Converting Enzyme (ACE) reduces blood pressure and gives an anti-hypertensive effect. Chicken skin is an undesirable by-product of the poultry industry, disliked by consumer because of the high fat content. The aim of this research is to determine the effect of molecular weight reduction on ACE inhibition activity in chicken skin hydrolysate. Chicken skin is prepared by manually defatting, soaked in acetone and in 0.1M phosphate buffer. Sample hydrolysis is carried out using alcalase enzyme for a duration of 4 hours at 60˚C and pH 9.5. The best degree of hydrolysis (DH), at 4th hour, with value of 49.54 ± 0.79 %, is ultrafiltrated and used in ACE inhibition activity detection. The sample weight ≥ 10 kDa , 3 – 10 kDa and ≤ 3 kDa contains 5.63 ± 0.01 g/L, 2.84 ± 0.06 g/L and 1.07 ± 0.18 g/L peptide content respectively whereas soluble protein content is 0.51 mg/mL for sample weight ≥ 10 kDa, 0.27 mg/mL for sample weight 3 – 10 kDa and 0.23 mg/mL for sample weight ≤ 3 kDa. The ACE inhibition activity in sample weight ≤ 3 kDa is highest with value of 80.38 ± 2.69% followed by sample weight 3 – 10 kDa with a value of 49.40 ± 2.63% and sample weight ≥ 10 kDa with value of 42.73 ± 5.08%. Significant differences ( P ≤ 0.05) exist between sample weight ≤3 kDa and > 3 kDa. This research shows that molecular weight reduction increases ACE inhibition activity.